Motorcycle Tourism in the Philippines: An Assessment of the 5 A’s of Tourism as a Basis for Sustainable Development Planning - Abad, Mark Alvin H.; Nueda, Kelvin Julius A. (International Review of Management and Marketing, 2026)
Motorcycle tourism has emerged as a growing niche within the Philippine tourism industry, offering riders an adventurous and flexible way to explore multiple destinations. This study assessed motorcycle tourism in the Philippines using the Five A’s of Tourism framework—Attractions, Accessibility, Accommodation, Activities, and Amenities—as a basis for sustainable development planning. Employing a descriptive-quantitative research design, data were collected from 211 motorcycle tourists through structured survey questionnaires, with Gabaldon, Nueva Ecija serving as a representative site for national-level analysis. Results revealed that motorcycle tourists are predominantly young, male, and adventure-oriented, preferring short to medium-length trips while visiting multiple destinations per journey. Findings showed strongly positive perceptions of Attractions, Activities, and Amenities, particularly scenic landscapes, adventure opportunities, rest stops, and fuel and repair facilities. Accessibility and Accommodation were rated positively but moderately, indicating areas for improvement such as clearer signage, rider-specific services, and secure parking. The study also identified moderate challenges related to road safety and infrastructure, environmental sustainability, seasonality and weather conditions, limited motorcycle-friendly amenities, and regulatory and policy constraints. Based on these findings, a Proposed Development Plan Matrix and a Sustainable Motorcycle Tourism Development Framework were formulated to guide coordinated, inclusive, and environmentally responsible tourism development. The study provides empirical insights to support policy formulation and strategic planning for sustainable motorcycle tourism in the Philippines.